(untitled) (CIPEEX, 2022)
INTRODUCTION: DIABETES MELLITUS (DM) CAN BE UNDERSTOOD AS A DISORDER OF METABOLISM, CHARACTERIZED AS CHRONIC AND MULTIFACTORIAL ETIOLOGY, THEREFORE, LINKED TO OTHER COMPLICATIONS SUCH AS HYPERGLYCEMIA, ALTERED INSULIN EXCRETION, RESULTING DIRECTLY IN THE REDUCTION OR COMPLETE INHIBITION OF GLUCOSE UPTAKE THROUGH TISSUES (FAEDA, DE LEON, 2006). OBJECTIVE: THE GENERAL OBJECTIVE OF THIS STUDY WAS TO DESCRIBE HOW NURSING CARE IS PROVIDED TO THE PATIENT WITH DIABETES MELLITUS (DM) IN A FAMILY HEALTH STRATEGY (ESF) IN THE CITY OF GOIANPOLIS-GO. METHODOLOGY: THE QUALITATIVE TYPE WAS DEVELOPED FOR THE DEVELOPMENT OF THE RESEARCH, WHICH WAS STRUCTURED IN THE MUNICIPALITY OF GOIANPOLIS, A CITY LOCATED IN THE INTERIOR OF THE STATE OF GOIS, WHERE 5 NURSES AND 4 NURSING TECHNICIANS WERE INTERVIEWED (OLIVEIRA, 2002). THE MATERIAL WAS OBTAINED THROUGH INTERVIEWS WITH PROFESSIONALS, AND THE ANALYSIS WAS STRUCTURED ACCORDING TO WHAT WAS PROPOSED BY MINAYO (2009). RESULTS: DATA ANALYSIS RESULTED IN FOUR CATEGORIES, FOLLOWED BY ITS SUBCATEGORIES: NURSING ACTIONS VERSUS PATIENT ASSISTANCE WITH DIABETES MELLITUS, PERMANENT EDUCATION BY THE NURSING TEAM, STRATEGIES TO OBTAIN ADHERENCE TO TREATMENT AND RECEPTION BY THE NURSING TEAM . CONCLUSION: THE INTERVIEW CONTENT SHOWED THAT FROM THE PERSPECTIVE OF THE INTERVIEWEES, THE EDUCATIONAL ACTIONS TO BE PUT INTO PRACTICE WERE FUNDAMENTALLY LINKED TO THE FOLLOW-UP OF DIETS, ADEQUATE USE AND REGULATION OF MEDICATIONS AND REGULAR MEASUREMENTS OF THE GLYCEMIC LEVEL. THE PARTICIPATION OF FAMILY MEMBERS IN THE TREATMENT OF THE INDIVIDUAL HAS NOT YET BEEN PRESENT AS DESIRABLE, BEING THIS DIRECT RESULT OF THE LACK IN THE EDUCATION ACTIONS THAT INTEGRATE THE FAMILY IN THE PROCESS. EVEN THOUGH THERE WERE NOT ENOUGH ACTIONS FOR FAMILY INVOLVEMENT IN THE TREATMENT PROCESS, NURSING PROFESSIONALS RECOGNIZE THE IMPORTANCE OF THESE EDUCATIONAL ACTIONS, SINCE THEY MAKE POSSIBLE THE SCIENCE OF RISK FACTORS AND THE EXTENDED PERMANENCE IN THE TREATMENT OF THE DISEASE.